Pontine lesion in opsoclonus-myoclonus syndrome shown by MRI. Issue 12 (December 1988) - Hattori, T; Hirayama, K; Imai, T; Yamada, T; Kojima, S
Abstract : Two patients with opsoclonus-myoclonus syndrome are reported whose magnetic resonance imaging (MRI) showed brain stem lesions. Both patients developed the opsoclonus-myoclonus syndrome after an upper respiratory illness. One case had visual hallucinations during the course of illness and MRI revealed a focal lesion in the pons involving the junction of basis and tegmentum. MRI of the second case showed a focal lesion at the upper pontine tegmentum.